2005
DOI: 10.1016/j.orthres.2004.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive low-energy shock wave application without local anesthesia is more efficient than repetitive low-energy shock wave application with local anesthesia in the treatment of chronic plantar fasciitis

Abstract: Background: It remains unclear whether application of local anesthesia (LA) interferes with clinical efficacy of extracorporeal shock wave therapy (ESWT) for chronic plantar fasciitis. Aims: To evaluate the effect of local anesthesia on the clinical outcome after repetitive low-energy ESWT for chronic plantar fasciitis. Methods: Eighty-six patients with chronic plantar fasciitis were randomly assigned to receive either low-energy ESWT without

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
94
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 53 publications
3
94
0
3
Order By: Relevance
“…The efficacy and safety of ESWT on chronic PF have been demonstrated in several randomized clinical trials. [22][23][24][25][26] ESWT causes extreme excitement of the axon, destroys unmyelinated sensory fibers, improves symptoms by initiating an inflammatory response to the secretion of growth factors or nitrous oxide and revitalizes tissues by increasing angiogenesis. 3,9 Some researchers have reported that ESWT is effective in the treatment of PF in comparison to a control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy and safety of ESWT on chronic PF have been demonstrated in several randomized clinical trials. [22][23][24][25][26] ESWT causes extreme excitement of the axon, destroys unmyelinated sensory fibers, improves symptoms by initiating an inflammatory response to the secretion of growth factors or nitrous oxide and revitalizes tissues by increasing angiogenesis. 3,9 Some researchers have reported that ESWT is effective in the treatment of PF in comparison to a control group.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 This discrepancy may be explained by methodological differences. For example, the use of local anesthesia, 23,29,30 applicator position, 23 and the use of different energy densities of ESWT 31 are all factors that may have affected study results. In a study by Lee et al, 31 a medium-energy (0.16 mj/mm 2 ) ESWT group showed statistically significant pain reduction and improved function scores compared to a low-energy (0.08 mj/mm 2 ) group.…”
Section: Discussionmentioning
confidence: 99%
“…A reduced pain level was reported for patients who additionally stretching exercised three times or more each week [41]. Rompe et al [42] and Labek et al [43] showed that the use of anesthesia can reduce the efficacy of the shockwaves. It was also demonstrated as the high-energy shock waves decreased the painful symptoms [44][45][46].…”
Section: Shock Wavesmentioning
confidence: 99%
“…In contrast, high-energy shock wave therapy can be applied in one visit but requires local anesthesia. Controversy revolves around whether the use of anesthesia compromises clinical outcomes [35]. In theory, the infiltration of local anesthesia may interfere with the focusing of the shock wave to the site of maximal discomfort [35].…”
Section: Extracorporeal Shock Wave Therapymentioning
confidence: 99%
“…Controversy revolves around whether the use of anesthesia compromises clinical outcomes [35]. In theory, the infiltration of local anesthesia may interfere with the focusing of the shock wave to the site of maximal discomfort [35]. Also local anesthesia may alter the inflammatory response and angiogenesis ESWT invokes.…”
Section: Extracorporeal Shock Wave Therapymentioning
confidence: 99%